À Rebours : La rebelión informalista (1939-1968) - Centro Atlántico de Arte Moderno, Las Palmas de Gran Canaria; Museo Nacional Centro de Arte Reina Sofía; Angulo, Gonzalo; Ashton, Dore; Bartelik, Marek; Blanco, Maria Dolores Jeménez; Brey, Mariano Rajoy; Chirino, Martin; Craven, David; Guirao Cabrera, José; Hayashi, Michio; Licht, Fred; et al. (Las Palmas de Gran Canaria : Centro Atlantico de Arte Moderno, 1999)
Alechinsky, Pierre ; Appel, Karel ; Auerbach, Frank ; Bacon, Francis ; Baziotes, William ; Bomberg, David ; Borduas, Paul-Emile ; Borges, Jacobo ; Brooks, James ; Brzozowski, Tadeusz ; Burki, Alberto ; De Szyszlo, Fernando ; Diebenkorn, Richard ; Domoto, Hisao ; Dubuffet, Jean ; Fautrier, Jean ; Fontana, Lucio ; Francis, Sam ; Giacometti, Alberto ; Gorky, Arshile ; Guerrero, José ; Guston, Philip ; Hilton, Roger ; Imaï, Toshimitsu ; Jorn, Asger ; Kantor, Tadeusz ; Kawabata, Minoru ; Kline, Franz ; Kolar, Jiri ; Lam, Wifredo ; Louis, Morris ; Maccio, Romulo ; Martinez, Raúl ; Masson, Andre ; Matta (Roberto Antonio Sebastian Matta Echaurren) ; Millarès, Manuel ; Mitchell, Joan ; Morales, Armando ; Motherwell, Robert ; Noé, Luis Felipe ; Noël, Georges ; Pollock, Jackson ; Resnice, Milton ; Rothko, Mark ; Saura, Antonio ; Scott, William ; Sima, Joseph ; Soulages, Pierre ; Stamos, Theodoros ; Sterne, Hedda ; Still, Clyfford ; Sugimata, Tadashi ; Tal-Coat, Pierre ; Tobey, Mark ; Tworkov, Jack ; Tàpies, Antoni ; Vedova, Emilio ; Wols ; Yoshihara, Jiro ; Zaritsky, Josef ; de Kooning, Willem ; de Staël, Nicolas
biografie
À Rebours : La rebelión informalista (1939-1968) / The Informal Rebellion (1939-1968), Centro Atlantico de Arte Moderno, Las Palmas de Gran Canaria / Museo Nacional Centro de Arte Reina Sofia, 1999
Spaans
Spaans & Engels
boek
Keywords: Japan; Spanje; U.S.A.